Uterine Lipoleiomyoma-An Interesting Entity/Research Article - ABHIJIT.S.ACHARYA,; SACHIN.B.INGLE, (International Journal of Pharma and Bio Sciences, 2012)
Lipoleiomyomas are unusual benign neoplasms of uterus and are considered to be a variant of uterine myomas. Their reported incidence varies from 0.03 to 0.2%. When a large uterine tumor is found in perimenopausal or postmenopausal woman, the possibility of malignancy should be considered.. These tumors generally occur in asymptomatic obese perimenopausal or menopausal women. We here in report an incidentally diagnosed extremely unusual case of uterine lipoleiomyoma.